Kiddo disleksia mobile application: a dyslexia screen tool in Malay language - Nopiah, Julaina; Mohamed Nor, Mohd Faizal; Jofri, Muhamad Hanif; Mohamed Ali, Mohd Hatta; Bahrudin, Ida Aryanie; Omar, Abdul Halim; Abd Rahman, Nor Rasida (UTEM, 2019)
Identification of potential dyslexic among Malaysia student is crucial to ensure earlier intervention is given. Current practice in the Malaysian school system, screening test has been given based on teacher’s observation and intervention. The low number of student enrol in special education indicate this task is difficult. It is due to untrained and lack of awareness regarding dyslexia among Malaysia teacher. Therefore, the easy, simple and accurate screen test tool are required. Kiddo Disleksia, a dyslexia screening tool based on mobile application has been designed and developed. The application exploits the uses of text, video, audio and graphic in multimedia to screen student with dyslexia based on visual and auditory. Kiddo Disleksia is developed by using Malay language as it’s specifically develops for student in earlier learning to recognize and distinguish the alphabet. Besides, this application able to use as learning tool for dyslexia student to identify alphabet letter and phonic (alphabet sound). The mobile gamed based approach is used to screen the student with fun and innovative way. A usability study has been conducted towards 20 dyslexia students and result shows 85% of respondent feel the application able to help them learn easier. They agree that Kiddo Disleksia able to screen the dyslexia student with fun and easy way.